COHESION IN ANNE HATHAWAY’S SPEECH TEXT ON “PAID PARENTAL LEAVE IS ABOUT CREATING FREEDOM TO DEFINE ROLES” - Utomo, Slamet; Sekti, Dita Indah (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2019)
This research aims to identify the grammatical and lexical cohesion used in Anne Hathaway’s speech text on “Paid Parental Leave is about Creating Freedom to Define Roles”, and interpret how grammatical and lexical cohesion are used in Anne Hathaway’s speech text on “Paid Parental Leave is about Creating Freedom to Define Roles”.The type of this research is descriptive qualitative research. The result of this research shows that all types of grammatical and lexical cohesion are used in the speech text. For the grammatical cohesions are: reference (personal, demonstrative and comparative reference), substitution (nominal substitution), ellipsis (verbal and clausal ellipsis) and conjunction (additive, adversative, causal and temporal conjunction). Meanwhile, the lexical cohesions are: reiteration (repetition, synonym, superordinate and general word) and collocation. The most dominant of cohesive devices used in the speech text is reference especially for personal reference. All those cohesive devices are used clearly, it means that the speech text of Anne Hathaway entitled “Paid Parental Leave is about Creating Freedom to Define Roles” used grammatical and lexical cohesion well. Finally, the writer suggests that cohesion is important to be studied in language learning because cohesion can be used as a strategy to construct and comprehend any text especially for speech.